Análisis de las estrategias comunicacionales externas gestionadas por la Dirección de Comunicación del Municipio de Loja, en la emergencia sanitaria; generada a partir de la presencia de la (covid19) en la ciudad de Loja, durante el periodo: 15 marzo - 15 de septiembre del 2020. - Torres Siavichay, Fredy Daniel (2021)
This work was done in the field of institutional communication, carried out in a public service entity such as the Municipality of Loja. The research consisted of a descriptive and expository analysis of the different external communication strategies implemented by the Communication Department ofthe Municipality of Loja, to relate with users in the most critical period of the pandemic, determining the effectiveness and scope of the releases issued in the main social networks of the institution, such as Facebook, Twitter, and Instagram; considering the number of reactions that reached three of the most popular publications, three tables were used for this, that made it possible to count the number of reactions, to compare them with the number of inhabitants of the city of Loja. Additionally, to know the opinion of the public, 387 surveys were conducted to users of the Municipality of Loja, where it was found that there is a great lack of knowledge about external communication campaigns and a regular-deficient opinion about the communication services provided by the Municipality. Finally, a semiotic analysis of two arts was carried out, that disseminated official communications of a massive nature on the official social networks of the institution, based on the interview of Monica Maldonado Espinoza, who teaches classes of the semiotics of the image; likewise, four more interviews were taken that allowed to know in detail the field of research and its development, to achieve the proposed objectives.